An approach to the notions about welfare regimes: Manuel Mora and Rodney Arismendi, political agents of the Communist Party of Costa Rica and the Communist Party of Uruguay, 1958 - Morales Rivera, Valeria (2021)
This work aims to make a comparison between the notions about welfare regimes, exposed by two political referents of the Latin American left, specifically Manuel Mora Valverde and Rodney Arismendi. The above, as a contribution to the history of concepts in the region, which allows reconstructing the meanings that processes, institutions and situations had for different actors. As the main result of this exercise, both leaders presented dissonant meanings with each other, which oscillated between supporting or rejecting the welfare regimes implemented in the respective countries. Beyond the characteristics of the states in each country, it is intended to delve into the way in which each of the chosen agents carried out their respective reconstruction.